Explaining the technological cooperation of knowledge and business ecosystems: an approach based on ecotone and ambidextrous organization theories - Bahman Norouzpour; Mahmoud Moradi; Mohamad Rahim Ramezanian; Mostafa Ebrahimpour Azbari (تصمیم گیری و تحقیق در عملیات)
Purpose: In recent years, concepts such as the fifth generation university, the fifth generation of industry and society have been continuously raised among the researchers. The university's success in the fifth mission and formation of the fifth generation of industry and society requires considering that both university and industry are the main actors of knowledge and business ecosystems. Without considering the comportment of these actors in the context of ecosystems, it is impossible to form a proper communication process between these institutions. Therefore, the paper aims to develop a conceptual model to explain the cooperation between knowledge and business ecosystems.Methodology: This research is interpretive from a philosophical point of view and inductive from the point of view of theory development. The research strategy is "Grounded Theory," which presents a conceptual model. The systematic procedure of Strauss and Corbin was used to create a suitable structure for better understanding and classification of data and findings. Two methods, Member Checking or Participant Feedback and Review by External Audit, were used to check the validity of the data. Furthermore, a fixed index or re-test reliability was used to check the reliability of the research findings.Findings: The results show that to form cooperation between industry and university as the main actors of business and Knowledge ecosystems, 18 key and vital categories should be considered. A conceptual model is presented to describe the relationship between these categories.Originality/Value: It can be claimed that despite the studies conducted in the field of cooperation between industry and university, a model for this cooperation has not been developed so far, and only the challenges of this cooperation have been discussed, or a series of concepts have been discussed. In this research, an attempt has been made to present such a model by taking into account theories such as ecotone and ambidextrous organization, and various aspects of this cooperation have been investigated.